2011
DOI: 10.1186/ar3270
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood lead levels are associated with radiographic and symptomatic knee osteoarthritis: a cross-sectional analysis in the Johnston County Osteoarthritis Project

Abstract: IntroductionLead (Pb) is known to affect bone, and recent evidence suggests that it has effects on cartilage as well. As osteoarthritis (OA) is a highly prevalent disease affecting bone and cartilage, we undertook the present analysis to determine whether whole blood Pb levels are associated with radiographic and symptomatic OA (rOA and sxOA, respectively) of the knee.MethodsThe analysis was conducted using cross-sectional data from the Johnston County Osteoarthritis Project, a rural, population-based study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Even metabolic processes in the bone are adversely affected by Pb [44,45,60,63,85]. Further Pb has been stated as a potential risk factor for osteoporosis [23], has negative influences on bone healing mechanisms [96] and might affect the articular cartilage tissue [24]. In the present study no significant differences in the trace element content and distribution pattern between bones from individuals with osteoporotic neck fractures and those from age matched healthy individuals without fractures could be detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even metabolic processes in the bone are adversely affected by Pb [44,45,60,63,85]. Further Pb has been stated as a potential risk factor for osteoporosis [23], has negative influences on bone healing mechanisms [96] and might affect the articular cartilage tissue [24]. In the present study no significant differences in the trace element content and distribution pattern between bones from individuals with osteoporotic neck fractures and those from age matched healthy individuals without fractures could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to Pb is associated with chronic diseases in the nervous, hematopoietic, skeletal, renal and endocrine systems [21,22]. Pb has been stated also as a potential risk factor for osteoporosis [23] and osteoarthritis [24]. Approximately 95% of the total body Pb burden is stored in skeleton [25] indicating that the bone tissue has a high capacity to accumulate and store Pb.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on environmental exposure and OA have suggested that increasing levels of whole blood lead exposure is associated with small but significant increases in the prevalence and severity of radiographic knee OA [94]. It is currently unclear whether or not this association is explained by a direct toxic effect of lead on joint tissues or through an indirect mechanism, however this preliminary research suggests that features of the environment, such as environmental exposure to this toxicant may play some role in mobility and disability in knee OA.…”
Section: Studies Of Social Determinants and Oa Outcomesmentioning
confidence: 99%
“…Our results suggest that systemic Pb is associated with bone turnover (uNTX-I), as well as mineralized (uCTX-II) among women, and non-mineralized (COMP) cartilage turnover among men, but as this is a cross-sectional analysis, we cannot determine whether cartilage turnover is an indicator, or consequence, of Pb release. The association between blood Pb level and cartilage-associated biomarkers, along with our recent cross-sectional analysis showing associations between blood Pb and radiographic knee osteoarthritis and knee symptoms (Nelson et al 2011), suggests the possibility that Pb may play a role in the pathophysiology of osteoarthritis. Longitudinal studies including assessments of radiographic and symptomatic osteoarthritis, in conjunction with both blood and bone Pb, would be valuable to further evaluate the potential effects of Pb on joint symptoms, onset and progression of this highly prevalent and often debilitating disease.…”
Section: Discussionmentioning
confidence: 72%